2022
DOI: 10.1002/jmv.27769
|View full text |Cite
|
Sign up to set email alerts
|

Assessing nonsexual transmission of the human papillomavirus (HPV): Do our current cleaning methods work?

Abstract: Human papillomavirus (HPV) is thought to be sexually transmitted; however, there have been a few studies investigating a possible iatrogenic source of infection.Therefore, it is important to assess the cleaning methods of reusable medical devices. This study assessed whether cleaning methods of flexible endoscopes in an otolaryngology clinic are effective against HPV. There were 24 patients with a history of head and neck cancer in the study; however, two outliers were excluded.Nine patients were confirmed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Nosocomial transmission of the HPV is also possible which may occur during the use of transvaginal ultrasound probe which is commonly used in the Obstetrics & Gynaecology departments where the probe is placed very close to the cervix which may act as a pathway of infection [56]. Like the instruments used in the Obstetrics and Gynaecology department, flexible endoscopes used in otolaryngology may also serve as a source of infection in the oral region [58]. 3% of the probes were found to be positive for HPV DNA after examination and 1.9% were found to be positive in pre-examination samples [59].…”
Section: Transmission Of Hpvmentioning
confidence: 99%
“…Nosocomial transmission of the HPV is also possible which may occur during the use of transvaginal ultrasound probe which is commonly used in the Obstetrics & Gynaecology departments where the probe is placed very close to the cervix which may act as a pathway of infection [56]. Like the instruments used in the Obstetrics and Gynaecology department, flexible endoscopes used in otolaryngology may also serve as a source of infection in the oral region [58]. 3% of the probes were found to be positive for HPV DNA after examination and 1.9% were found to be positive in pre-examination samples [59].…”
Section: Transmission Of Hpvmentioning
confidence: 99%
“…Tucker et al concluded current endoscope reprocessing methods do not eliminate human papillomavirus (HPV) and may allow it to be transmitted from carriers to other otolaryngology clinic patients. The authors suggested that orthophthalaldehyde (OPA) high‐level disinfectant (HLD) “may not be fully effective at removing HPV from endoscopes.” 1 We believe the evidence does not support their conclusions, and we are concerned that problems with study design and reprocessing quality may have contributed to erroneous conclusions.…”
mentioning
confidence: 94%